Perceived stress, quality of life, and coping skills among patients with schizophrenia in symptomatic remission - Sheikh Shoib; Soumitra Das; Anoop Krishna Gupta; Tamkeen Saleem; Sheikh Mohd Saleem (Middle East Current Psychiatry, 2021)
Abstract Background Schizophrenia is one of the worst diseases with its ubiquitous challenges due to its unique psychopathology and life events. Patients with schizophrenia use various coping strategies to overcome distress. The aim of the study was to evaluate the association between perceived stress, quality of life, and coping skills in patients with schizophrenia in remission. A total of 48 consecutive patients of schizophrenia, in remission, attending outpatient department of psychiatry at Academic hospital, South India, who satisfied the inclusion and exclusion criteria were recruited for the present study. The participants were assessed on Positive and Negative Symptoms Scale, Ways of Coping Checklist – Revised and Perceived Stress Scale and WHO Quality of Life. Results were analyzed using appropriate statistical package software v 16.0. Result Highest medial was found in self-controlling and positive reappraisal coping skills. Distancing is associated with high physical domain of quality of life whereas patients with good social support score more in social and physical domain of quality of life. Conclusion Patients with history of schizophrenia even though in remission dwell a stressful life. They often need different kind of social support or cognitive aids. In that view, studying their stress level, ability to cope with it, and quality of life will help us to manage them in better way.